Etika a statistika: neprípustné prístupy k datům - Haas, T (Casopis lekaru ceskych, 2000)
The objective of the paper is to draw attention to incorrectness of various statistical approaches to research data. We critically assess the situation when first the decision on the hypothesis to be proved is done and then data are made to fit the hypothesis. We demonstrate that data cannot be satisfactorily interpreted without close attention to the manner of their collection. Finally we criticize opportunistic data torturing when researcher explores the data until a significant result is found and then devises a biologically plausible hypothesis.
Keywords: výzkum; statistika jako téma; Ethics, Professional; profesionální etika; Statistics as Topic; Research